Amantes que se desvanecen en el tiempo: la memoria etnográfica o la compleja significación de las leyendas - Díaz González de Viana, Luis (Revista de Antropología Social, 2008)
Myths and legends are not so distant from rumour or tales as has often been believed, for they share -frequently- the same topics. But, in contrast to the later -which are momentary or clearly not temporary- myth and legend furthermore constitute a little known and yet very important part of collective memory. Their accounts allude to both the past and the present of peoples, contributing to the shaping of a continuous time and memory which -by having been studied especially from an anthropological perspective- we could designate as “ethnographical”. Through the analysis of the complex formation of some legends, this paper suggests that there exists some sort of “truth” in the legendary: that tell us something important about the view held by some peoples of themselves and of others.